Teen Motherhood and Academic adjustment of Re-Admitted Girls in Mixed day Secondary Schools of Bondo Sub-County, Kenya: Implications for School Counseling. - Maundu, Janet K. (JOOUST, 2015)
Teen motherhood and the related problem of dropout has become a matter of public concern in Kenya today, Re-admission, Retention policies and the Affirmative action program have been put in place, but due to lack of legal backing or guidelines on how the implementation should be done, these policies are weak. The purpose of this study was to explore teen motherhood and academic adjustment of re-admitted girls in mixed day secondary schools of Bondo Sub-county Kenya: Implication for school counseling. Objectives of the study were: to explore teen motherhood and academic adjustment of re-admitted girls; to determine whether social stigma affects academic adjustment of re-admitted teen mothers: to establish whether teen mother hood affects self-esteem and academic adjustment of re-admitted girls: and to establish the strategies for academic adjustment of re-admitted teen mothers. Theories such as Person-Centered and Resilience were used to inform the study. A mixed methods approach was adopted and within it the concurrent triangulation design was used. All the teen mothers re-admitted in secondary schools of Bondo were targeted. Purposive sampling technique was used to select the schools while snowball sampling technique was used to identifys the re-admitted teen mothers with a sample size of 100 re-admitted teen mothers accessed. Teen motherhood, social stigma, self-esteem and strategies for academic adjustment Questionnaires for re-admitted teen mothers were used to collect quantitative data while interview schedules for re-admitted teen mothers were used to collect qualitative data. Quantitative data was analyzed through inferential statistics while qualitative data was analyzed through thematic analysis. Reliability of the questionnaire was ensured by split-half reliability of Spearman-Brown Formulae and a coefficient of 0.832 was reported. Validity was ensured by expertise judgment of lecturers of Jaramogi Oginga Odinga University of Science and Technology. Reliability of the interview was ensured through member checks (piloting) and external audits The findings were that, re-admitted teen mothers were struggling to adjust to school work despite having high self-esteem; and that, although re¬admitted teen mothers were adjusting to school work. They suffered stress caused by social stigma; that re-admitted teen mothers identified guidance and counseling, acceptance hard work, ambition regular class attendance and self-motivation as some of their strategies for academic adjustment. The study recommended that, the Ministry of Education Science and Technology should employ full time counselors in all counties to co-ordinate programs that support re-admitted teen mothers' education and allocate resources for the support of re¬admitted teen mothers education in secondary schools; School Principals should identity and keep a record of all the re-admitted teen mothers in the school for proper planning: teacher counselors should form peer counseling groups for only the re-admitted teen mothers; teachers should involve re-admitted teen mothers in activities that stimulate high self-esteem and adopt individualized teaching approach for re-admitted teen mothers.
Keywords: Teen motherhood.; School Counseling.; Kenya; Re-Admission of Teen Mother into School.